1998
DOI: 10.2223/jped.437
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of four schemes for vivax malaria treatment in children

Abstract: Objetivo: A cura da malaria vivax permanece dificultada por um fator determinante de recaídas: a duração do tratamento. Em Belém, a observação de que um grande número de pacientes com malaria vivax curava-se, a despeito do abandono do tratamento, levou à concretização deste estudo objetivando avaliar a eficácia de esquemas mais operacionais para malária em crianças. Métodos: Foi realizado ensaio clínico prospectivo e randomizado, em 200 crianças com malaria vivax, atendidas ambulatorialmente. Variáveis observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 10 publications
0
9
0
2
Order By: Relevance
“…Also, regional studies already describe high relapse rates when one-half dose or less PQ is provided. 2,14,25,26,37 Finally, we found that an incomplete PQ regimen results in nearly 30% recurrence over 6 months, suggesting that studies with arms without radical cure drugs could induce preventable relapses.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Also, regional studies already describe high relapse rates when one-half dose or less PQ is provided. 2,14,25,26,37 Finally, we found that an incomplete PQ regimen results in nearly 30% recurrence over 6 months, suggesting that studies with arms without radical cure drugs could induce preventable relapses.…”
Section: Discussionmentioning
confidence: 70%
“…report relapse rates of 20-30% 13,14,23,24 and even 36-57%. 25,26 Additionally, in our low-dose regimen, we observed that the actual dose received may be further associated with the risk of relapse.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…376 were duplicated and 251 articles were screened, out of which 229 were excluded. Twenty-three articles were fully read for review in the second phase, out of which 9 clinical trials met with the eligibility criteria; 7 studies for the qualitative systematic review of the primary objective 15 - 21 , out of these, 4 studies made a comparison with the standard regimen and were included in the meta-analysis 15 , 17 , 19 , 20 , the other 3 did not compare with the standard regimen 16 , 18 , 21 . Three studies for the secondary objective were identified 19 , 22 , 23 , one of which was also included in the primary objective; only one study made a comparison with the standard regimen 19, therefore, no studies for the quantitative synthesis of this objective were included ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 shows the main characteristics of the studies. Three studies were conducted in Brazil 15 , 16 , 18 , two in Peru 17 , 20 , one in Colombia 21 , one in India 19 , one in Pakistan 22 , and one in Indonesia 23 . Only one study was conducted in a non-endemic region where reinfection during the follow-up was not possible 23 .…”
Section: Resultsmentioning
confidence: 99%